Revelation in the Qur'an : A Semantic Study of the Roots n-z-l and w-ḥ-y - Loynes, Simon P. (Texts and Studies on the Qurʾān, 2021)
"In Revelation in the Qur'an Simon P. Loynes presents a semantic study of the Arabic roots n-z-l and w-ḥ-y in order to shed light on the modalities of revelation in the Qur'an. Through an exhaustive analysis of their occurrences in the Qur'an as well as pre-Islamic poetry, Loynes argues that the two roots represent distinct occurrences in the Qur'anic concept of revelation, with the former concerned with spatial events and the latter with communicative. This has significant consequences for understanding the Qur'an's unique concept of revelation and how this is both in concord and at variance with earlier revelations"--